Perancangan Security Network Intrusion Prevention System Pada PDTI Universitas Islam Raden Rahmat Malang - Farid Wahyudi; Listanto Tri Utomo (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Security is very main in computer networks, where many devices are connected to each other to interact and exchange data without limits. Network security is also a very important issue to prioritize, one of which is to use an intrusion prevention system. At PDTI UNIRA there are often network security problems, one of which is that during the test season, the server experiences many intrusion problems. The purpose of this research is to develop a social science system based on the analysis at PDTI of Raden Rahmat Islamic University Malang. This research method uses a computer security development approach, namely the Intrusion Prevention System (IPS), by combining firewall engineering methods and Intrusion-Detection System (IDS). The result of this research is a technology that can be used to prevent attacks that will enter the local network checking and recording all data packets and recognizing sensor packets, when the attack has been identified, IPS will deny access (block) and record (log) all data packets. identified. So IPS acts as a firewall that will allow and block combined with IDS that can detect packets in detail. With a network security system, the Unira PDTI server is safer and can avoid intrusion.